PR001 gene therapy improved phenotypes in models of Parkinson's disease with GBA1 mutation: Molecular and cell biology/endosomal‐lysosomal dysfunction. (7th December 2020) - Sheehan, Patty; Heckman, Laura D.; Fenn, Tim; Wong, Li Chin; Nelson, Stuart; Garimalla, Swetha; Haller, Jorge; Daily, Jenn; Politi, Jason; Dai, Yong; Hefti, Franz; Abeliovich, Asa
Abstract: Background: Mutations in GBA1, which result in deficiency of lysosomal enzyme glucocerebrosidase (GCase), are the most common known genetic cause of Parkinson's disease (PD). Decreased GCase activity in PD patients with GBA1 mutations (PD‐GBA) causes accumulation of glycolipid substrates, which leads to lysosomal dysfunction and neuroinflammation. With our gene therapy product candidate, PR001, we aim to increase GCase activity in PD‐GBA patients in order to ameliorate the lysosomal dysfunction and slow or stop disease progression. Method: GCase activity and α‐Synuclein levels were assessed following PR001 treatment in vitro in a cell line and in primary rodent neurons. Two mouse models of GCase deficiency that display phenotypic characteristics consistent with PD‐GBA, including decreased GCase activity, glycolipid substrate accumulation, motor behavioral phenotypes, and neuroinflammation, were used to assess the efficacy of PR001 in vivo . Safety endpoints were examined in the two mouse models as well as in nonhuman primates. Result: PR001 treatment in vitro increased GCase activity and decreased α‐Synuclein levels. In PD‐GBA models in vivo, PR001 treatment increased GCase activity, decreased glycolipid substrate accumulation, improved motor abnormalities, and decreased neuroinflammation. These therapeutic benefits were persistent, with lasting effects observed at 6 months post‐treatment. Safety studies demonstrated that PR001 was well tolerated at all doses tested. Conclusion: Overall, PR001 displayed efficacy in multiple independent cell and animal models of PD‐GBA and no PR001‐related safety events or adverse findings in mice and nonhuman primates. These findings demonstrate that PR001 is a promising potential gene therapy for PD‐GBA patients. We have recently initiated a Phase 1/2 clinical trial to investigate safety, tolerability, and effects on biomarkers and measures of clinical efficacy.